The Influence of Pharmacy Officer Performance on Service Quality and Its Implications for Patient Satisfaction at the Regional Health Center of Pulang Pisau Regency, Central Kalimantan - Sulistini, Kiki; Rindu , Rindu (Sean Institute, 2024)
Puskesmas is an operational entity that functions as a center for health development. Community health centers must prioritize the quality of health services, including ensuring accessibility and costs of treatment through pharmaceutical services. There are several obstacles that hinder the implementation of patient-centered pharmaceutical services, resulting in poor performance and reduced service quality. These obstacles include: 1) Excessive workload, 2) Insufficient drug supplies, 3) Inadequate availability of pharmacists, 4) Ambiguous guidelines for carrying out these activities, and 5) Limited communication with doctors and other health workers. This research was conducted at the Pulang Pisau Regency Regional Health Center, Central Kalimantan with the aim of analyzing the performance of pharmacy officers on the quality of health services. The research was conducted from October 2023 to February 2024 using a mix method, namely a combination of qualitative and quantitative methods in the form of descriptive analytics with a cross sectional study design. Data collection was carried out through interviews and questionnaires. Data analysis was carried out using qualitative and quantitative methods. Univariate and bivariate analyzes were performed, and the chi-square statistical test was used. The analysis was carried out using SPPS version 25. It is hoped that the results of this research can become program policy recommendations in an effort to improve the quality of health services to the community through improving the performance of pharmacy staff which has an impact on patient satisfaction.